TRACE ELEMENT ANALYSIS OF UREILITES: NEW CONSTRAINTS ON THEIR PETROGENESIS - Spitz A.H.; Boynton W.V. (My University, 1991)
Ureilites including ALHA77257, ALH82130, PCA82506, Kenna, and Novo Urei were analyzed using neutron activation analysis for Ca, Sc, Cr, Mn, Fe, Co, Ni, Zn, Ga, REE, W, Re, Os, Ir, and Au. Bulk and acid-treated samples were examined. It is concluded that trace elements provide additional constraints on the models for the petrogenesis of ureilites. The siderophile element abundances call for simplified models of chemical processing. REE concentrations imply multistage processing to produce the ureilites.